Collaborative Navigation and Negotiation of Jewish Texts Online: The Case of Project Zug as a Digital Havruta Platform. Issue 2 (3rd April 2022) - Goldfarb Cohen, Shai
ABSTRACT: We know little currently about how new digital tools have effected changes in Jewish studies learning environments and processes – although technologies play a central role in contemporary discussions of learning. This study aims to understand how learners collaboratively interpret Jewish sacred texts using informal online collaborative learning platforms. This case study focuses on Project Zug, an online havruta (paired couple) platform for the learning of Jewish texts. Based on 13 semi-structured interviews with Project Zug participants and using sociocultural frameworks of learning, I present how Project Zug created a digital havruta community of practice enabling dynamic learning identities.